2004
DOI: 10.1152/japplphysiol.01273.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human muscle Na+-K+-ATPase in vitro during prolonged exercise is increased with hypoxia

Abstract: This study investigated the effects of prolonged exercise performed in normoxia (N) and hypoxia (H) on neuromuscular fatigue, membrane excitability, and Na+-K+ -ATPase activity in working muscle. Ten untrained volunteers [peak oxygen consumption (Vo2peak) = 42.1 +/- 2.8 (SE) ml x kg(-1) x min(-1)] performed 90 min of cycling during N (inspired oxygen fraction = 0.21) and during H (inspired oxygen fraction = 0.14) at approximately 50% of normoxic Vo2peak. During N, 3-O-methylfluorescein phosphatase activity (nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 56 publications
2
44
2
Order By: Relevance
“…These findings suggest that the impairment in neuromuscular function, measured before and after the progressive exercise, is attributable to sites other than the sarcolemma. In this regard, our findings confirm our earlier research using a prolonged exercise protocol, namely that the neuromuscular deficit that occurs with Norm and Hypox cannot be explained by a failure in membrane excitability (50). The results of the current study indicate that although using a test protocol in hypoxia severely blunts power output, compromises V O 2 peak , disrupts energy homeostasis, and depresses Na ϩ and K ϩ membrane transport potential, membrane excitability does not appear to be limiting.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings suggest that the impairment in neuromuscular function, measured before and after the progressive exercise, is attributable to sites other than the sarcolemma. In this regard, our findings confirm our earlier research using a prolonged exercise protocol, namely that the neuromuscular deficit that occurs with Norm and Hypox cannot be explained by a failure in membrane excitability (50). The results of the current study indicate that although using a test protocol in hypoxia severely blunts power output, compromises V O 2 peak , disrupts energy homeostasis, and depresses Na ϩ and K ϩ membrane transport potential, membrane excitability does not appear to be limiting.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that a failure in membrane excitability secondary to reductions in maximal Na ϩ -K ϩ -ATPase activity may explain the lower mechanical PO and lower peak aerobic power observed in hypoxia compared with normoxia (46,47). Support for this possibility comes from a recent study published by our group in which we have shown a greater reduction in maximal Na ϩ -K ϩ -ATPase activity during prolonged submaximal exercise when performed in hypoxia compared with normoxia (50). Although, we could find no evidence for a greater impairment in neuromuscular function during submaximal exercise in hypoxia, such may not be the case with progressive exercise.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…At near-maximum exercise intensities, however, cardiac output, limb blood flow, and arteriovenous O 2 difference may not be able to compensate for reduced O 2 delivery. These factors may explain why a previous study did not find an effect of hypoxia on muscle fatigue as a result of moderateintensity, submaximal whole body exercise (44).…”
Section: Eiah Contributes To Locomotor Muscle Fatiguementioning
confidence: 89%
“…With the exception of the tissue samples, all other procedures and measurements were performed during the 3-day exercise protocol. We have previously reported that providing exercise patterns and dietary habits are not substantially altered, a wide range of muscle cellular properties remain stable over a similar time frame (15,69).…”
Section: Experimental Conditionsmentioning
confidence: 99%